94.5k views
4 votes
Solve 7(y + 2) – (4y – 10) = 44 – 2y + 5
A.y = -5
B.y = 5
C.y = -10

User David Loy
by
4.3k points

2 Answers

3 votes

Answer:

y=5

Explanation:

7(y+2)-(4y-10) = 44-2y+5 distribute on the left and combine like terms on the right side of the equation

7y + 14 -4y +10 = 49 - 2y move every term with a variable on the left side with a change sign and the numbers on the right side

7y-4y+2y =49 -14 -10

5y = 25 divide both sides by 5

y5/5=25/5 so

y=5

User Nemke
by
4.7k points
7 votes

Answer:

y = 5

Explanation:

7(y + 2) – (4y – 10) = 44 – 2y + 5

(7y+14) - (4y - 10) = 49 -2y

3y +24 = 49 -2y

5y +24 = 49

5y = 25

y = 5

User Anton Valqk
by
4.6k points